Gene Expression, Activity and Localization of Beta-Galactosidases during Late Ripening and Postharvest Storage of Tomato Fruit - Fanourakis, Dimitrios; Nikoloudakis, Nikolaos; Paschalidis, Konstantinos A.; Christopoulos, Miltiadis, V; Goumenaki, Eleni; Tsantili, Eleni; Delis, Costas; Tsaniklidis, Georgios (My University, 2022)
Beta-galactosidases (β-GALs) hold a key role in both fruit softening and the increase of total soluble solids during maturation. Despite determining both quality and potential postharvest longevity, β-GAL activity during ripening, with a special focus on the postharvest period, has not been adequately addressed in a spatial and temporal manner. This study focused on the regulation of gene expression in relation to the total β-GAL enzyme activity during the ripening of tomato fruit attached on the plant, as well as harvested fruit ripened for 5 d at 4, 10, or 25 °C. The transcription of genes coding for β-GAL isoenzymes was significantly affected by both the fruit maturation stage (unripe vs. red ripe) and postharvest storage temperature. Cold stressed tomatoes (4 °C) exhibited a remarkably higher transcription of most β-GAL genes compared to on-plant red ripe fruit and to fruit exposed to either 10 or 25 °C, indicating a low temperature response. However, enzymatic activity and water-soluble pectin content increased with elevated temperature exposure, peaking in fruit stored at 25 °C. β-GAL activity was present in the pericarp, while it was less detected in locular parenchyma. These findings highlight the dual role of β-GAL not only in maturation, but also in the metabolism during postharvest homeostasis and cold acclimation of tomato fruit.
Keywords: beta-galactosidase; cold stress; fruit quality; gene expression; Solanum lycopersicum L; soluble pectins